THE INDONESIAN LINGUISTIC VALIDATION OF THE URETERAL STENT SYMPTOMS QUESTIONNAIRE - Tansol, Christiano; Noegroho, Bambang Sasongko; Safriadi, Ferry; Sani, Wildan (Indonesian Urological Association, 2019)
Objective: To validate the Indonesian version of the ureteral stent symptoms questionnaire (USSQ) for patients with indwelling ureteral stents. Material & Methods: The Indonesian version of the USSQ was developed following a well-established multistep process by two urologists and two independent translators. A total of 38 patients with indwelling temporary unilateral ureteral stents completed the Indonesian USSQ. Patients completed questionnaires at 1 week after stent insertion and 1 week after stent removal. The reliability of the Indonesian version was evaluated for internal consistency using Cronbach’s alpha test. Domain structures were examined by interdomain (section) associations using Spearman’s correlation coefficient (r). Sensitivity to change of each domain was assessed using Wilcoxon test. Results: Urinary, pain, general health, work performance and additional problem showed good internal consistency whereas sexual problem and global quality of life displayed low consistency. There were strong correlations of urinary symptoms with body pain (r=0.633) and general health (r=0.686), moderate correlation with work performance. In addition there was also strong correlation between body pain and general health (r=0.723). Sensitivity to change were significant to all domain except sexual matters domain. (p<0.001). Conclusion: The Indonesian USSQ is reliable and can be utilize as a tool to investigate symptoms and to assess quality of life related issues due to ureteral stents in Indonesian patient.